Surgeon’s physical and mental stress while performing laparoscopic cholecystectomy - Joshi, Mukund Raj; Bohara, Tanka P; Parajuli, Anuj; Rupakheti, Shail (Journal of Kathmandu Medical College, 2017)
Background: Laparoscopic cholecystectomy is performed either by four port or three port. Although the overall patient outcome has been studied with comparable results, surgeon’s stress level has not been addressed commonly.Objective: To compare the difference in surgeon’s physical and mental stress between three port and four port laparoscopic cholecystectomy.Methods: This prospective randomized comparative study was carried out from January 2014 to August 2014 in patients undergoing laparoscopic cholecystectomy with American technique. Patients were randomized into four port laparoscopic cholecystectomy group and three port laparoscopic cholecystectomy group. Surgery was performed by experienced laparoscopic surgeons. At the end of procedure, surgeons were given questionnaire to evaluate physical and mental stress faced by them based on Visual Analogue Scale. The results obtained were compared.Results: Total 60 cases were evaluated, 30 in each group. Mean age of patients and American society of Anesthesiologists score were not different. Surgeon’s perception regarding physical and mental stress while performing in two different groups was analyzed. The difference is not statistically significant. Neither any of the three port group needed to add additional port nor any of the patients were converted to open surgery. None of the patient in either group developed clinically significant complication.Conclusion: Both the four and three port laparoscopic cholecystectomy techniques are comparable in regards to patient outcome as well as to the physical and mental stress experienced by the surgeons.